Better Together: Synergic Effect of Gallium‐Based Catalyst and Porous Support for Reduction Reactions - Jimenez Sanchez, Marco Aurelio; Carl, Simon; Taccardi, Nicola; Haumann, Marco; Apeleo Zubiri, Benjamin; Wasserscheid, Peter; Spiecker, Erdmann; Vogel, Nicolas; Bachmann, Julien; Magnabosco, Giulia (ChemCatChem, 2024)
Liquid metal solutions are a new class of catalysts with outstanding properties in terms of catalytic conversion and resistance to coking. Finding the perfect combination of catalytic particles with homogeneous size distribution and support material able to stabilize them during catalysis is key for preparing model systems to gain understanding of these complex catalytic processes. In this work, we present a method for the preparation of small and narrowly distributed gallium–palladium particles supported on inverse opals, interconnected 3-D porous networks with a very narrow pore size distribution. Our platform is a promising candidate as supported liquid metal catalytic system thanks to its permeability to fluids and its confined pore environment, which prevents the coalescence of the metal alloy, thus maximizing the surface area available for the catalytic reaction. We demonstrate their enhanced performance when compared to other state of the art systems giving a proof of concept of their application as catalysts for a simple model reaction, the reduction of methylene blu